Legal Relationship Between Platform Service Providers and Online Transportation Driver as Gig Workers (Platform Workers) - Hadiati, Dian; Abdul Rachmad Budiono; Hanif Nur Widhiyanti (The Islamic Education and Multiculturalism Foundation, 2023)
This research aims to determine the classification of legal relationships between platform service providers and online transportation drivers as gig workers (platform workers). The choice of theme is motivated by the fact that so far the legal relationship that occurs between platform service providers and online transportation drivers is a partnership relationship, but the partnership relationship that occurs does not implement the principles of partnership in its implementation in the business world. This partnership cooperation relationship is not regulated in the Law Number 20 of 2008 regarding Micro, Small, and Medium Enterprises or the Indonesian labour law because the Indonesian labour law only recognizes working relationships, while in the Law Number 20 of 2008 regarding Micro, Small, and Medium Enterprises because the original intent of the partnership in Law No.20/2008 is very different from the partnership relationship that is currently happening between platform service providers and online transportation drivers. Then the writing of this paper uses a normative juridical method with a statutory approach and an analytical approach. The legal material obtained by the author will be analyzed using descriptive analytical analysis techniques, namely a method of analyzing legal material by determining the content or meaning of legal rules in terms of partnership cooperation relationships, as well as the Civil Code. From the results of research with the above methods, the classification of legal relationships between platform service providers and online transportation drivers as gig workers (platform workers) is classified as a partnership relationship based on the Subordinate union of partnership, namely a partnership based on the merger of two or more parties that are subordinately related